PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KECERDASAN INTRAPERSONAL SISWA DI SMA N 1 GUNUNG TOAR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Arif Budiman; Wigati Iswandhiari; Andrizal Andrizal (Universitas Islam Kuantan Singingi, 2020)
Based on the writer's initial observations at SMA N 1 GunungToar, several symptoms were found in the field, among others: many students were late coming to school, were not serious in learning, were easily influenced by the environment and said that was not good, therefore the writer was interested in researching about the role of PAI teachers in developing students' intrapersonal intelligence atGunungToar 1 High School, which aims to find out the role of PAI teachers in developing students' intrapersonal intelligence and to determine the factors that influence the Role of Islamic Religious Education Teachers to develop students'intrapersonal intelligence outside the teaching and learning process in SMA N 1 GunungToar, KuantanSingingi District by interview observation and documentation, then the data were analyzed with descriptive qualitative. The results of this studyare Islamic religious education teachers have brought quite good results in developing intrapersonal intelligence of students at SMA N 1 GunungToar, withactivities carried out outside the teaching and learning process such as the Flag Ceremony every Monday, Kultum every Friday, Dzuhurprayer congregation, commemorating Islamic Holidays, and class meeting activities. These activities seem to have an effect on students' intrapersonal intelligence, this is evidenced by students who are no longer late coming to school, are serious in learning and can control themselves well. Whereas previously many students were late coming to school, were not serious in learning, were easily influenced by the environment and said things that were not good.